The Effectiveness of Compassion-Focused Therapy on Loneliness and Cognitive Flexibility in Elderly Men - Maryam Tohidifar (Alzahra University, 2021)
The phenomenon of aging is the result of the natural course of time, which leads to physiological, psychological and social changes. Considering the accelerating growth of the aging population and the fact that the elderly suffers from reduced cognitive flexibility and feelings of loneliness due to old age and reduced abilities; Therefore, this study was performed to determine the effectiveness of compassion- focused therapy on loneliness and cognitive flexibility in elderly men. The research method was quasi-experimental with pretest-posttest design with a control group. The statistical population of the study was the elderly male in Ahvaz in 2020. The sample size consisted of 30 elderly men (60 to 70 years old) who were selected by convenience sampling method and according to the inclusion criteria. The experimental group received Therapeutic intervention in 8 weeks and 8 sessions of 90 minutes. The questionnaires used in this study included Dennis and Vanderwall Cognitive Flexibility Questionnaire and Russell Loneliness Questionnaire. Data were analyzed by univariate analysis of covariance. The results showed that there was a significant difference between the experimental and control groups in terms of loneliness and cognitive flexibility. In other words, compassion-focused therapy reduced loneliness and increased cognitive flexibility in the elderly. Consistent with the findings of the present study, compassion- focused therapy can be suggested as an effective method to reduce feelings of loneliness and increase cognitive flexibility in the elderly.